2014
DOI: 10.2146/ajhp130165
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hepatotoxicity associated with fluoroquinolones: A national case–control safety study

Abstract: The findings of a national VA safety study suggested an increased hepatotoxicity risk asssociated with fluoroquinolone exposure in the study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 51 publications
1
45
0
2
Order By: Relevance
“…The VA Healthcare System operates 151 medical centers and 827 community-based outpatient clinics throughout the US [19]. Inpatient and outpatient care is captured electronically in each VA healthcare facility through the electronic medical record system, which has been in place since 1999 [20].…”
Section: Methodsmentioning
confidence: 99%
“…The VA Healthcare System operates 151 medical centers and 827 community-based outpatient clinics throughout the US [19]. Inpatient and outpatient care is captured electronically in each VA healthcare facility through the electronic medical record system, which has been in place since 1999 [20].…”
Section: Methodsmentioning
confidence: 99%
“…This report found that the chronic administration of ciprofloxacin could cause the up-regulation of CYP2E1 in mouse microsomes using Western blot analysis [33] . Recent clinical investigation has indicated a significant association between ciprofloxacin use and an increased risk of hepatotoxicity [34,35] . This hepatotoxicity has resulted from the induction of the drug metabolizing enzyme CYP2E1 by the administration of ciprofloxacin.…”
Section: Wwwnaturecom/aps Liu L Et Almentioning
confidence: 99%
“…The current focus of many clinical trials on serious adverse drug reactions may not adequately address treatment tolerance, which substantially affects treatment adherence and outcomes in programmatic settings. Thus, many adverse drug reactions, which are frequently dose-dependent and aggravated by co-morbidities (especially those with organ dysfunction and ageing 4,5 ), are often insufficiently evaluated in clinical trial settings but highly pertinent at both patient care and programme implementation levels when a very large patient population is involved. The need of clinical vigilance and diligent monitoring for all potential toxicities associated with high-dose moxifloxacin is imperative, especially for cardiotoxicity, which necessitates periodic electrocardiographic assessment throughout the treatment for all patients, with possibly 24-h Holter monitoring for selected cases to comprehensively detect potentially dangerous arrhythmia.…”
mentioning
confidence: 99%